Effects of disinfectants against norovirus virus‐like particles predict norovirus inactivation. (23rd September 2016) - Sato, Jun; Miki, Motohiro; Kubota, Hiromi; Hitomi, Jun; Tokuda, Hajime; Todaka‐Takai, Reiko; Katayama, Kazuhiko
ABSTRACT: Human noroviruses (NoVs) are a major cause of epidemic and sporadic acute gastroenteritis worldwide. Public and personal hygiene is one of the most important countermeasures for preventing spread of NoV infection. However, no a practicable cell culture system for NoV had been developed, initial tests of the virucidal effectiveness of anti‐NoV disinfectants and sanitizers have been performed using surrogate viruses. In this study, NoV virus‐like particles (VLPs) were used as a new surrogate for NoVs and a method for evaluating NoV inactivation using them developed. This method is based on morphological changes in VLPs after treatment with sodium hypochlorite. VLP specimens were found to become deformed and degraded in a concentration‐dependent manner. Based on these results, the effects of sodium hypochlorite on VLPs were classified into four phases according to morphological changes and number of particles. Using the criteria thus established, the efficacy of ethanol, carbonates and alkali solutions against VLPs was evaluated. Deformation and aggregation of VLPs were observed after treatment with these disinfectants under specific conditions. To determine the degradation mechanism(s), VLPs were examined by SDS‐PAGE and immunoblotting after treatment with sodium hypochlorite and ethanol. The band corresponding to the major capsid protein, VP1, was not detected after treatment with sodium hypochlorite at concentrations greater than 500 ppm, but remained after treatment with ethanol. These results suggest that VLPs have excellent potential as a surrogate marker for NoVs and can be used in initial virucidal effectiveness tests to determine the mechanism(s) of chemical agents on NoVs.